Case of inverted papillary urothelial carcinoma in the ureter. Issue 2 (2nd December 2021) - Nirei, Takuma; Nakaigawa, Noboru; Matsumura, Mai; Kataoka, Toshiaki; Nagasaka, Takahiro; Aomori, Kota; Ito, Yusuke; Muraoka, Kentaro; Yao, Masahiro
Abstract : Introduction: Urothelial neoplasms with a varus growth pattern are rare, and few urologists have encountered inverted urothelial carcinoma of the ureter. Case presentation: An 82‐year‐old man was referred to our hospital for investigation of gross hematuria. Magnetic resonance imaging revealed nodules measuring 1–2 mm in diameter in the left upper ureter with slight reduction in signal intensity on diffusion‐weighted imaging. Ureteroscopy showed a pedunculated smooth tumor that had the appearance of an inverted papilloma rather than the papillary shape typical of urothelial carcinoma. The tumor was biopsied and histopathological examination revealed a noninvasive, low‐grade urothelial carcinoma with inverted multiple layers. Laparoscopic radical nephroureterectomy was subsequently performed, and a pedunculated tumor measuring 20 mm in diameter was found in the left upper ureter. The histopathological diagnosis was inverted papillary urothelial carcinoma, low‐grade, pTa, pN0. Conclusion: This report provides the first clinical description of inverted papillary urothelial carcinoma of the ureter.